Phase Locking of Auditory-Nerve Fibers to the Envelopes of High-Frequency Sounds: Implications for Sound Localization - Dreyer, Anna (2006)
Although listeners are sensitive to interaural time differences (ITDs) in the envelope of high-frequency sounds, both ITD discrimination performance and the extent of lateralization are poorer for high-frequency sinusoidally amplitude-modulated (SAM) tones than for low-frequency pure tones. Psychophysical studies have shown that ITD discrimination at high frequencies can be improved by using novel transposed-tone stimuli, formed by modulating a high-frequency carrier by a half-wave–rectified sinusoid. Transposed tones are designed to produce the same temporal discharge patterns in high-characteristic frequency (CF) neurons as occur in low-CF neurons for pure-tone stimuli. To directly test this hypothesis, we compared responses of auditory-nerve fibers in anesthetized cats to pure tones, SAM tones, and transposed tones. Phase locking was characterized using both the synchronization index and autocorrelograms. With both measures, phase locking was better for transposed tones than for SAM tones, consistent with the rationale for using transposed tones. However, phase locking to transposed tones and that to pure tones were comparable only when all three conditions were met: stimulus levels near thresholds, low modulation frequencies (<250 Hz), and low spontaneous discharge rates. In particular, phase locking to both SAM tones and transposed tones substantially degraded with increasing stimulus level, while remaining more stable for pure tones. These results suggest caution in assuming a close similarity between temporal patterns of peripheral activity produced by transposed tones and pure tones in both psychophysical studies and neurophysiological studies of central neurons.